2021
DOI: 10.1088/1755-1315/640/5/052022
|View full text |Cite
|
Sign up to set email alerts
|

Development of a technology for polysaccharide-based film coating

Abstract: This work describes the design of a film coating based on polysaccharides of bacterial and plant origin with several methods of application (by spraying, brushing and wrapping) on food. We used the bacterial polysaccharide xanthan as a thickener, the plant polysaccharide carboxymethyl cellulose (CMC) as a structurant, and the biological additive lecithin as a plasticizer. Depending on the film coating application method, concentrations of the studied polymers were selected with the same component composition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Previously, we have developed film coatings [11,12], applied to food products in different ways: by spraying, brushing, and wrapping. These packaging materials had such advantageous organoleptic characteristics as transparency, uniformity, density, lack of taste and odor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have developed film coatings [11,12], applied to food products in different ways: by spraying, brushing, and wrapping. These packaging materials had such advantageous organoleptic characteristics as transparency, uniformity, density, lack of taste and odor.…”
Section: Resultsmentioning
confidence: 99%
“…In the course of the experiment, film coatings were made with several concentrations of polysaccharides, xanthan and CMC (%): 0.60 and 2.73 (spraying); 0.90 and 2.05 (brushing); 1.61 and 1.38 (wrapping), respectively. These concentrations were taken because we previously showed that such concentrations are optimal for the design of film coatings on food products for application in various ways [11,12].…”
Section: Resultsmentioning
confidence: 99%
“…The thickness of polysaccharide films with incorporated compounds can be influenced by several factors. Beloglazova et al [36] observed that the concentration of polysaccharides influenced the appearance and thickness of the films. Cado et al [37] reported that the simultaneous spraying of chitosan, hyaluronic acid and alginate resulted in a linear increase in thickness with spraying time.…”
Section: Thickness and Moisture Contentmentioning
confidence: 99%